2011
DOI: 10.1002/ijc.25908
|View full text |Cite
|
Sign up to set email alerts
|

Association of tissue promoter methylation levels of APC, TGFβ2, HOXD3 and RASSF1A with prostate cancer progression

Abstract: Aberrant promoter methylation is known to silence tumor-suppressor genes in prostate cancer (PCa). We correlated quantitative promoter methylation levels of APC, TGFb2 and RASSF1A in 219 radical prostatectomies diagnosed between 1998 and 2001 with clinicopathological follow-up data available including Gleason Pattern (GP), Gleason Score (GS) and pathological stage and explored their potential in predicting biochemical recurrence using univariate and multivariate analyses. We observed that the average methylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 30 publications
8
78
1
Order By: Relevance
“…Aberrations to DNA methylation in certain GP morphologies require further investigation as it may improve personalized patient treatment by utilizing biomarker information. The DNA methylation of APC, CYP26A1, HOXD3, HOXD8, RASSF1, TBX15 and TGFβ2 genes were investigated in the current study, as they have previously been revealed as promising prognostic biomarkers for PCa with the potential for clinical utility in independent patient cohorts (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Aberrations to DNA methylation in certain GP morphologies require further investigation as it may improve personalized patient treatment by utilizing biomarker information. The DNA methylation of APC, CYP26A1, HOXD3, HOXD8, RASSF1, TBX15 and TGFβ2 genes were investigated in the current study, as they have previously been revealed as promising prognostic biomarkers for PCa with the potential for clinical utility in independent patient cohorts (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted from 10 µm sections of previously prepared FFPE blocks matching the selected H&E slides using a QIAamp DNA Mini kit (Qiagen, Inc., Valencia, CA, USA), as previously described (23)(24)(25). DNA methylation was analyzed in the same GP4 area used for histological evaluation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations